RA09.01: NORMAL LYMPH NODE APPEARANCE IN THE THORAX. (14th September 2018) - Hansen, Tomas; Nilsson, Magnus; Lindholm, Daniel; Sundström, Johan; Hedberg, Jakob
Abstract: Background: Modern treatment of esophageal cancer is multimodal and highly dependent on detailed diagnostic assessment of clinical stage which includes nodal stage. Clinical appraisal of nodal stage requires knowledge of normal radiological appearance, information of which is scarce. We aimed to describe lymph node appearance on computed tomography (CT) investigations in a randomly selected cohort of healthy subjects. Methods: In a sample of 426 healthy Swedish volunteers aged 50–64 years, CT scans were studied in detail concerning intrathoracic node stations relevant in clinical staging of esophageal cancer. With stratification for sex, the short axis of visible lymph nodes was measured and distribution of lymph node sizes was calculated as well as proportion of patients with visible nodes above 5 and 10 millimeters for each station. Probability of having any lymph node station above 5 and 10 millimeters was calculated with a logistic regression model adjusted for age and sex. Results: In the 214 men (age 57.3 ± 4.1 years) and 212 women (57.8 ± 4.4years) included in the study, a total of 309 (72.5%) had a lymph node with a short axis of 5 mm or above was seen in one of the node stations investigated. When using 10 mm as a cutoff, nodes were visible in 29 (6.81%) patients. Men had three times higher odds of having any lymph node with short axis 5 mm or above (OR 3.03 95% CI 1.89–4.85, P  < 0.001) as well as 10mm or above (OR 2.31 95% CI 1.02–5.23, P  = 0.044) compared to women. Higher age was not associated with propensity for lymph nodes above 5 or 10 millimeters in this sample. Conclusion: In a randomly selected cohort of patients between 50 and 64 years, almost ten percent of the men and four percent of the women had lymph nodes above ten millimeters, most frequently in the subcarinal station (station 107). More than half of the patients had nodes above five millimeters on computed tomography and men were much more prone to have this finding. The probability of finding lymph nodes in specific stations relevant of esophageal cancer is now described. Disclosure: All authors have declared no conflicts of interest.